Rozwiązane

Oblicz wartość liczbową wyrażenia 2x(3+6a)= X=2. A=1





2 a-2a(5b+4)=
b) 5x +3x-2x =
C) 2x(3x-5) +4x=
d) 3a-5x+4a+5x =
E) -x(x-3a+1)=



Odpowiedź :

2x(3+6a)= 4(3+6)= 36

a-2a(5b+4)= a-10ab-8a= -7a-10ab

b) 5x +3x-2x = 6x

C) 2x(3x-5) +4x= 6x2 - 10x+4x=6x2-6x

d) 3a-5x+4a+5x = (3a+4a)+(−5x+5x)= 7a

E) -x(x-3a+1)= -x2+3xa-x

Odpowiedź:

2x(3 + 6a) = 6x + 12a = 6 * 2 + 12 * 1 = 12 + 12 = 24

x=2; a=1

2a - 2a(5b + 4) = 2a - 10ab - 8a = -6a - 10ab

b)

5x + 3x - 2x = 8x - 2x = 6x

C)

2x(3x - 5) + 4x = 6x² - 10x + 4x = 6x² - 6x

d)

3a - 5x + 4a + 5x = 7a

E)

-x(x - 3a + 1) = -x² + 3ax - x

Szczegółowe wyjaśnienie: